Flow visualization and images analysis (Dordrecht, 1993)
This book presents state-of-the-art research on teh techniques and their application to fluid flow. Progress in fluid mechanics depends heavily on the availability of good experimental data which can inspire new ideas and concepts but which are also necessary to check and validate theories and numerical calculations. With the advent of new recording and image analysis techniques new and promissing experimental methods in fluid flows have presented themselves which are able to obtain spatial information
Keywords: flow visualization,fluid mechanics - data processing,image processing